This action might not be possible to undo. Are you sure you want to continue?
2
2.1: APPLY ADVANCED DIFFERENTIATION FORMULAE AND IMPLICIT FUNCTIONS
2.1.1: Perform Differentiation of Inverse Trigonometric Functions
 USING FORMULA PROVIDED
 Calculations directly using formula
 Form of question → y = inverse trigonometric
 Example:
i. y = tan
1
x → u = x
ii. y = sin
1
5x → u = 5x
iii. y = tan
1
(2x1) → u = 2x1
iv. y = sin
1
(cos x) → u = cos x
v. y = sin
1
(
) → u =
vi. y = cosec
1
(1+x
2
) → u = 1+x
2
 Example (a)
Differentiate the following functions with respect to x:
i. y = sin
1
(cos x)
ii. y = sin
1
(
)
iii. y = cosec
1
(1+x
2
)
ADVANCED DIFFERENTIATION
u
FORMULA:






FORMULA:





12
Solution:
i. y = sin
1
(cos x)
Step 1: Identify the ‘u’ from the equation and find
u = cos x ,
=  sin x
Step 2: Determine the formula and replace the ‘u’ and
( )
dx
du
u
u
dx
d
2
1
1
1
sin
÷
=
÷
→ ( ) ) sin (
) (cos 1
1
cos sin
2
1
x
x
x
dx
d
÷ 
÷
=
÷
=
x
x
cos 1
sin
2
÷
÷
=
x
x
sin
sin
2
÷
=
x
x
sin
sin ÷
= 1
ii. y = sin
1
(
)
u =
,
=
( )
dx
du
u
u
dx
d
2
1
1
1
sin
÷
=
÷
→ 
.

\



.

\

÷
= 
.

\

÷
3
1
3
1
1
1
3
1
sin
2
1
x
x
dx
d
=


.

\

÷
9
1 3
1
2
x
=
9
9
3
1
2
x ÷
=
( )
2
9
9
1
3
1
x ÷


.

\

=
2
9 x ÷
iii. y = cosec
1
(1+x
2
)
u = 1+x
2
,
= 2x
( )
dx
du
u u
u
dx
d
1
1
cosec
2
1
÷
÷
=
÷
→ ( )
( ) ( )
( ) x
x x
x
dx
d
2
1 1 1
1
1 cosec
2
2 2
2 1

÷ + +
÷
= +
÷
=
( ) ( )
2 4 2
2 1
2
x x x
x
+ +
÷
=
( ) 2 1
2
2 2 2
+

.

\

+
÷
x x x
x
=
( ) 2 1
2
2 2
+ +
÷
x x
cos
2
x + sin
2
x = 1
1 – cos
2
x = sin
2
x
Try this!
Find
y
for the following:
a) y = tan
1
(2x1)
b) y = sin
1
5x
13
 USING PRODUCT RULE
 Calculations using product rule formula:
(
) (
)
 Form of question → y =
 Example:
i. y = x
2
sin
1
→ u = x
2
, v = sin
1
ii. y = 3 sin
1
(ln 2x) → u = 3 , v = sin
1
(ln 2x)
iii. y = x cos
1
x → u = x , v = cos
1
x
 Example (b)
Differentiate the following functions with respect to x:
i. y = x
2
sin
1
ii. y = 3 sin
1
(ln 2x)
iii. y = x cos
1
x
Solution:
i. y = x
2
sin
1
Step 1: Form of y = uv, identified the value of ‘u’ and ‘v’.
y = x
2
sin
1
u = x
2
v = sin
1
Step 2: Differentiate both ‘u’ and ‘v’. For ‘v’, refer formula from page 11.
u = x
2
→
= 2x v = sin
1
→
4
2
1 2
1
x
÷
=
Step 3: Use formula of product rule and simplify.
(
) (
)
(
) (
√
)
()
√
√
u
v
inverse trigonometric x
Differentiate sin
1
Differentiate
=
2
1
2
2
1
1

÷
=

.

\

x
14
√(
)(
)
√(
)
ii. y = 3 sin
1
(ln 2x)
u = 3 →
= 0 v = sin
1
(ln 2x) →
=
( )
2
2
1
2
1
1
2 ln
 
÷
x
x
=
( )
2
1
2 ln
1
x x ÷
(
) (
)
(
( )
2
1 2 ln
1
x x ÷
)
( )()
=
( )
2
2 ln 1
3
x x ÷
iii. y = x cos
1
x
u = x →
= 1 v = cos
1
x →
= 1
2
1
1

÷
÷
x
=
2
1
1
x ÷
÷
(
) (
)
(
√
)
()
= (
√
)
Differentiate sin
1
Differentiate cos
1
Try this!
Find
y
for the following:
a) y = (1  x
2
) sin
1
x
b) y = x tan
1
x
x 2.5 2.9 3.3 3.7 4.1 4.5
y
15
 USING QUOTIENT RULE
 Calculations using quotient rule formula:
(
)(
)
 Form of question → y =
 Example:
i. y =
→ u = tan
1
, v = x
ii. y =
→ u =
, v =
 Example (c)
Differentiate the following functions with respect to x:
i. y =
ii. y =
Solution:
i. y =
Step 1: Form of y =
, identified the value of ‘u’ and ‘v’.
u = tan
1
x , v = x
Step 2: Differentiate both ‘u’ and ‘v’. Refer formula from page 11 for any inverse trigonometric.
u = tan
1
x →
= 1
2
) ( 1
1

+ x
v = x →
= 1
Differentiate tan
1
Differentiate x = 1
16
Step 3: Use formula of quotient rule and simplify.
(
) (
)
=
(
)
()
()
=
(
)
=
(
)
=
(
)
ii. y =
u =
→
= 0 + 1
2
1
1

+ x
v =
→
= 0  (
)
= (
)
(
) (
)
(
) (
) (
)() (
)
(
)
(
)(
)
(
)
(
)(
)
Differentiate tan
1
Differentiate 3tan
1
x (use product rule):
u = 3 v = tan
1
x
= 0
=
Try this!
Find
y
for the following:
y =
co
x 2.5 2.9 3.3 3.7 4.1 4.5
y
17
2.1.2: Perform Differentiation of Hyperbolic Functions
 USING FORMULA PROVIDED
 Calculations directly using formula
 Form of question → y = hyperbolic functions
 Example:
i. y = cosh (7x + 2) → u = 7x + 2
ii. y = sinh 2x → u = 2x
iii. y = cosh (ln x) → u = ln x
 Example (d)
Differentiate the following functions with respect to x:
i. y = cosh (7x + 2)
ii. y = sinh 2x
iii. y = cosh (ln x)
Solution:
i. y = cosh (7x + 2)
Step 1: Identify the ‘u’ from the equation and find
u = 7x + 2 ,
= 7
Step 2: Determine the formula and replace the ‘u’ and
( )
dx
du
u u
dx
d
sinh cosh = → ( ) ( ) 7 2 7 sinh 2 7 cosh  + = + x x
dx
d
= 7 sinh (7x + 2)
ii. y = sinh 2x
u = 2x ,
= 2
( )
dx
du
u u
dx
d
cosh sinh = → ( ) 2 2 cosh 2 sinh  = x x
dx
d
= 2 cosh 2x
u
FORMULA:






18
iii. y = cosh (ln x)
u = ln x ,
=
( )
dx
du
u u
dx
d
sinh cosh = → ( ) ( ) 1
1
ln sinh ln cosh   =
x
x x
dx
d
( ) x
x
ln sinh
1
=
 USING PRODUCT RULE
 Calculations using product rule formula:
(
) (
)
 Form of question → y =
 Example:
i. y = x sinh x → u = x , v = sinh x
ii. y = e
3x
cosh x
2
→ u = e
3x
, v = cosh x
2
iii. y = x
3
sinh 2x → u = x
3
, v = sinh 2x
 Example (e)
Differentiate the following functions with respect to x:
i. y = x
3
sinh 2x
ii. y = x sinh x
iii. y = e
3x
cosh x
2
Solution:
i. y = x
3
sinh 2x
Step 1: Form of y = uv, identified the value of ‘u’ and ‘v’.
y = x
3
sinh 2x
u = x
3
v = sinh 2x
Try this!
Find
y
for the following:
a) y = ln (tanh x
3
)
b) y = coth (ln x
2
)
c) y = ech (
)
x 2.5 2.9 3.3 3.7 4.1 4.5
y
u
v
hyperbolic functions x
19
Step 2: Differentiate both ‘u’ and ‘v’. For ‘v’, refer formula from page 16.
u = x
3
→
= 3x
2
v = sinh 2x →
= 2 2 cosh  x = 2 cosh 2x
Step 3: Use formula of product rule and simplify.
(
) (
)
( ch ) h (
)
(ch )
h
ii. y = x sinh x
u = x →
= 1 v = sinh x →
= 1 cosh  x
(
) (
)
(ch ) h ()
ch h
iii. y = e
3x
cosh x
2
u = e
3x
→
= 3e
3x
v = cosh x
2
→
= x x 2
2
sinh 
= 2x sinh x
2
(
) (
)
( h
) ch
(
)
(h
)
ch
Differentiate sinh
Differentiate 2x = 2
Differentiate sinh
Differentiate cosh
20
 USING QUOTIENT RULE
 Calculations using quotient rule formula:
(
)(
)
 Form of question → y =
 Example:
i. y =
co
→ u = ch , v = x
2
ii. y =
(h )
→ u = (h ) , v =
iii. y =
co
→ u =
, v = ch
 Example (f)
Differentiate the following functions with respect to x:
i. y =
co
ii. y =
(h )
Solution:
i. y =
co
Step 1: Form of y =
, identified the value of ‘u’ and ‘v’.
u = ch , v =
Step 2: Differentiate both ‘u’ and ‘v’. Refer formula from page 16 for any hyperbolic functions.
u = ch →
= sinh 2x • 2 = 2 sinh 2x
v =
→
= 2x
Step 3: Use formula of quotient rule and simplify.
(
)(
)
( h )ch ()
( h ) ch
( ch )
( ch )
Differentiate 2x = 2 Differentiate tan
1
21
ii. y =
(h )
u = (h ) →
= x
x
cosh
sinh
1
 v =
→
= 3e
3x
(
)(
)
(
h
) (
)
(
)
ch
(ch )
ch
2.1.3: Perform Differentiation of Inverse Hyperbolic Functions
 USING FORMULA PROVIDED
 Calculations directly using formula
 Form of question → y = inverse hyperbolic
 Example:
i. y = sinh
1
x → u = x
ii. y = cosh
1
(3  2x) → u = 3  2x
iii. y = tanh
1
(
)→ u =
Differentiate ln:
Differentiate sinh:
ch
h
ch
u
FORMULA:






Try this!
Find
y
for the following: y =
co
x 2.5 2.9 3.3 3.7 4.1 4.5
y
22
 Example (g)
Differentiate the following functions with respect to x:
i. y = cosh
1
(3  2x)
ii. y = sinh
1
x
iii. y = tanh
1
(
)
Solution:
i. y = cosh
1
(3  2x)
Step 1: Identify the ‘u’ from the equation and find
u = 3  2x ,
= 2
Step 2: Determine the formula and replace the ‘u’ and
( )
dx
du
u
u
dx
d
1
2
1
1
cosh
÷
=
÷
→ ( ) ) 2 (
1
2
) 2 3 (
1
2 3
1
cosh ÷ 
÷ ÷
= ÷
÷
x
x
dx
d
=
1
2
) 2 3 (
2
÷ ÷
÷
x
=
1 9 12
2
4
2
÷ + ÷
÷
x x
=
) 2 3
2
( 4
2
+ ÷
÷
x x
=
) 2 3
2
(
1
+ ÷
÷
x x
ii. y = sinh
1
x
u = x ,
= 1
( )
dx
du
u
u
dx
d
2
1
1
1
sinh
+
=
÷
→ ( ) 1
2
1
1
1
sinh 
+
=
÷
x
x
dx
d
=
2
1
1
x +
iii. y = tanh
1
(
)
u = (
) ,
=
( ) 1 ,
2
1
1
1
tanh (
÷
=
÷
u
dx
du
u
u
dx
d
→
4
3
2
4
3
1
1
4
3
1
tanh 
÷
=
÷

.

\


.

\

x
x
dx
d
=


.

\

÷
16
2
9
1
3
4
x
=
2
9 16
12
x ÷
23
 USING PRODUCT RULE
 Calculations using product rule formula:
(
) (
)
 Form of question → y =
 Example:
i. y = (x
2
 1) tanh
1
x → u = x
2
 1 , v = tanh
1
x
ii. y = e
2x
cosh
1
x
→ u = e
2x
, v = cosh
1
x
iii.
 Example (h)
Differentiate the following functions with respect to x:
i. y = (x
2
 1) tanh
1
x
ii. e
2x
cosh
1
x
Solution:
i. y = (x
2
 1) tanh
1
x
Step 1: Form of y = uv, identified the value of ‘u’ and ‘v’.
y = (x
2
 1) tanh
1
x
u = x
2
 1
v = tanh
1
x
Step 2: Differentiate both ‘u’ and ‘v’. For ‘v’, refer formula from page 21.
u = x
2
 1 →
= 2x v = tanh
1
x →
= 1
2
1
1

÷ x
Try this!
Find
y
for the following:
a) y = sech
1
(sin x)
b) y = cosech
1
(tanh 2x)
x 2.5 2.9 3.3 3.7 4.1 4.5
y
u
v
inverse hyperbolic x
Differentiate tanh
1
Differentiate x = 1
24
Step 3: Use formula of product rule and simplify.
(
) (
)
(
) (
) (h
)()
(
) (h
)
ii. e
2x
cosh
1
x
u = e
2x
→
= 2e
2x
v = cosh
1
x →
= 1
1
2
1

÷ x
=
1
2
1
÷ x
(
) (
)
e
(
1
2
1
÷ x
) ch
(
)
(
1
2
2
÷ x
x
e
)
ch
Try this!
Find
y
for the following:
y = 3 sinh
1
√
x 2.5 2.9 3.3 3.7 4.1 4.5
y
This action might not be possible to undo. Are you sure you want to continue?
We've moved you to where you read on your other device.
Get the full title to continue listening from where you left off, or restart the preview.